2020
DOI: 10.1097/hjh.0000000000002667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Mediterranean diet on blood pressure: a systematic review and meta-analysis of randomized controlled trials and observational studies

Abstract: Objective: To conduct a systematic review and meta-analysis investigating effects of MedDiet on blood pressure in randomised controlled trials (RCTs) and associations of MedDiet with risk of hypertension in observational studies.Methods: PubMed, The Cochrane Library and EBSCOhost were searched from inception until January 2020 for studies that met the following criteria: 1) participants aged ≥18 years, 2) RCTs investigating effects of a MedDiet versus control on BP, 3) Observational studies exploring associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 75 publications
2
46
0
Order By: Relevance
“…This conclusion is in accordance with existing data from previously published studies that have reported a significant inverse correlation between adherence of MD and BP [ 131 , 132 ]. Moreover, two recent meta-analyses showed that MD could significantly reduce BP when compared to control diets [ 133 , 134 ]. In addition, a greater decrease in BP was recorded for subjects presented with higher BP at baseline and in studies with a longer duration of the intervention [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is in accordance with existing data from previously published studies that have reported a significant inverse correlation between adherence of MD and BP [ 131 , 132 ]. Moreover, two recent meta-analyses showed that MD could significantly reduce BP when compared to control diets [ 133 , 134 ]. In addition, a greater decrease in BP was recorded for subjects presented with higher BP at baseline and in studies with a longer duration of the intervention [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two recent meta-analyses showed that MD could significantly reduce BP when compared to control diets [ 133 , 134 ]. In addition, a greater decrease in BP was recorded for subjects presented with higher BP at baseline and in studies with a longer duration of the intervention [ 133 ]. Various nutrients included in MD exerted beneficial effects through improved vasodilation and endothelial function such as nitric oxides, flavonoids and minerals [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the study by Larsen et al [10] in 2006, which first demonstrated a BP lowering effect of sodium NO 3 − , there was a rapid surge in research testing the effects of dietary NO 3 − on health outcomes [89]. However, the research strategy in the last decade has almost taken an inverse approach to that typically adopted in nutritional science as the conduction of clinical trials have surpassed epidemiological investigations, which are generally considered as a first step to validate research hypotheses [90][91][92]. One of the primary reasons for the inverse trend is the lack of reliable and representative food databases of NO 3 − content to support an accurate dietary assessment [93].…”
Section: Other Lifestyle Factorsmentioning
confidence: 99%
“…However, in a recent analysis of over 8000 participants from the EPIC-Norfolk cohort (UK), we demonstrated that a 3 point increase in MedDiet score on a 14-point or 15-point scale was equivalent to between 1.5 and 5 fewer years of ageing on global cognition, with effects particularly evident in individuals at higher cardiovascular disease (CVD) risk. 16 Potential mechanisms of action for the MedDiet include improved cardiovascular health [17][18][19] and modulation of the gut microbiota 20 along with direct effects on brain glucose utilisation and β-amyloid load. 21 22 Increased PA has also been shown to reduce age-related cognitive decline and dementia risk.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%